2013
DOI: 10.1371/journal.pone.0080184
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis of Stimulus-Angle-Dependent Motor Control of Wind-Elicited Walking Behavior in the Cricket Gryllus bimaculatus

Abstract: Crickets exhibit oriented walking behavior in response to air-current stimuli. Because crickets move in the opposite direction from the stimulus source, this behavior is considered to represent ‘escape behavior’ from an approaching predator. However, details of the stimulus-angle-dependent control of locomotion during the immediate phase, and the neural basis underlying the directional motor control of this behavior remain unclear. In this study, we used a spherical-treadmill system to measure locomotory param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(66 citation statements)
references
References 47 publications
5
61
0
Order By: Relevance
“…1A), as described in a previous study (Oe and Ogawa, 2013). An animal was tethered on top of a Styrofoam ball using a pair of insect pins bent into an L-shape that were stuck to the cricket's tergite with paraffin wax.…”
Section: Treadmill Systemmentioning
confidence: 97%
See 3 more Smart Citations
“…1A), as described in a previous study (Oe and Ogawa, 2013). An animal was tethered on top of a Styrofoam ball using a pair of insect pins bent into an L-shape that were stuck to the cricket's tergite with paraffin wax.…”
Section: Treadmill Systemmentioning
confidence: 97%
“…Definition and calculation of these parameters were the same as those in our previous study (Oe and Ogawa, 2013). The x-and y-axes were defined as the lateral and antero-posterior axes of the cricket at the start position, respectively (Fig.…”
Section: Behavioral Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that ascending cercal sensory information is integrated with sensory input from other modalities within a higher center that includes the protocerebrum. It was recently reported that directional control of wind-elicited walking behavior requires descending signals from the cephalic ganglia [20], and it is suggested that directional information conveyed by GIs are processed within the brain, in which some multimodal local and descending interneurons responsive to cercal stimulation have been identified [28,31]. However, the specific brain region to which GIs transmit cercal sensory information is not known, and neuronal response properties including directional selectivity have not been investigated within the brain.…”
Section: Introductionmentioning
confidence: 99%